The influence of dietary fat level and crystalline amino acid additions on growth performance of 25- to 50-lb pigs - J Usry; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2003)
To determine the effects of increasing added fat on pig growth performance 1,440 pigs (each initially 26 lb) were used in a 21 d growth trial. Pigs were fed diets containing none, 1.5, 3.0, 4.5, and 6.0% choice white grease. Increasing added fat reduced (linear, P<0.05) ADFI and improved F/G. Although ADG was not significantly affected by fat level, increasing added fat from 0 to 1.5% or greater resulted in a 1-lb increase in total weight gain over the entire trial. The greatest improvement in feed efficiency was also observed with the addition of the first 1.5% fat; however, further increases in dietary fat continued to linearly reduce ADFI and improve F/G. These results would suggest that from 25 to 50 lb, 1.5 to 3.0% added fat optimized pig growth performance. Based on the results of Experiment 1, we conducted Experiment 2 to confirm the optimum level of added fat in combination with increased use of crystalline amino acids (3 vs 6 lb/ton L-lysine + other amino acids) to meet the pig's lysine requirements. In Experiment 2, 1,152 pigs (each initially 21 lb) were fed one of four dietary treatments arranged in a 2 x 2 factorial. Main effects included added fat (3 or 6%) and crystalline amino acid amounts (3 vs 6 lb/ton Llysine HCl with other amino acids added to maintain proper amino acid to lysine ratios). No differences were observed in growth performance, but based on current ingredient prices, reducing the amount of soybean meal by the use of higher levels of crystalline amino acids increased margin over feed cost. In conclusion, these data indicate that 3% added fat will optimize growth performance and margin over feed costs, and that the use of greater amounts of crystalline amino acids (up to 6 lb/ton L-lysine with added L-threonine and DL methionine) are efficiently used by the pig and will also help further increase margin over feed costs.; Swine Day, 2003, Kansas State University, Manhattan, KS, 2003
Keywords: Swine day; 2003; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 920; Kansas Agricultural Experiment Station contribution; no. 04-120-S; Pigs; Growth; Synthetic amino acids; Fat; Swine